Al-Qur’an Portrays Women’s Bodies: Critical interpretation of verses on existence, freedom, and morality - Nurhalimah, Hany (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2023)
The oppression of women often stems from the body and the way a person or tradition interprets it. From ancient times to the present, the history of women's bodies has always been about the history of oppression; that is, about the fate of women's bodies in the face of patriarchal culture. When women's bodies often become symbols of various forms of oppression, then liberating women must start from their liberation efforts that are embodied in patriarchal biased interpretations, both formal and cultural interpretations. At this point, there is a need for an interpretation that departs from other possibilities in understanding verses related to women. The focus of the study presented in this paper is trying to criticize the interpretations related to the verses of existence, freedom and morality of women interpreted through Merleau Ponty's phenomenology of perception. This stems from the author's basic assumption, when the Qur'an is understood as rahmatan lil alamin, it is impossible for the Qur'an to produce discriminatory interpretations.